Drug retention, inactive disease and response rates in 1860 patients with axial spondyloarthritis initiating secukinumab treatment : routine care data from 13 registries in the EuroSpA collaboration - Michelsen, Brigitte (2021)
© Author(s) (or their employer(s)) 2020. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.